In vitro anti-cholinesterase and anti-oxidant activity of three standardised polyherbal products used for memory enhancing in ethnomedicine of South-East Nigeria - Nwidu, Lucky Legbosi; Elmorsy, Ekramy; Carter, Wayne (Penerbit Universiti Sains Malaysia, 2018)
Background: Polyherbal standardised extracts used in ethnomedicine of Eastern Nigeria for memory improvements were evaluated for anti-cholinesterases and anti-oxidant properties.